The influence of creativity, communication, and digital literacy on understanding scientific culture and problem solving skills of biology students - Jamaluddin, Asham Bin; Palennari, Muhiddin; HS, Syamsul Bahri; Rosba, Evrialiani; Fatmawati, Any (Universitas Negeri Jakarta, 2025)
Understanding scientific culture (USC) and developing problem-solving skills (PSS) are important elements in facing complex global challenges in the digital era. This study examines the effects of creativity (CRV), communication (CMN), and digital literacy (DGL) on USC and PSS in biology students at Universitas Negeri Makassar, Universitas PGRI Sumatera Barat, and Universitas Pendidikan Mandalika in Indonesia. A cross-sectional quantitative survey approach was used with a structured online questionnaire, and data were analyzed using the Structural Equation Modeling (SEM) method. The results showed that CRV had a significant direct effect on USC and PSS. CMN also had an effect on USC. However, the direct effect of CMN on PSS was not significant, indicating that its role in improving problem-solving skills was mediated by USC. In contrast, DGL showed a weaker direct effect on PSS and USC, indicating a less dominant role than creativity and communication. These findings emphasize the importance of a synergistic educational approach that integrates CRV, CMN, and DGL to support USC and PSS. Emphasis on creativity as a transformative tool and communication as a collaborative medium in scientific contexts is highly recommended, while DGL needs to be further developed to effectively complement these competencies. Future research needs to explore these relationships in different contexts to refine educational strategies and address evolving challenges.